Klasifikasi Kelompok Varietas Unggul Padi Menggunakan Modified K-Nearest Neighbor - Aldion Cahya Imanda; Nurul Hidayat; Muhammad Tanzil Furqon (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Supreme varieties is a kind of varieties that produced from the cross of local supreme varieties. The main idea is to produce the best rice varieties. Nowadays the supreme varieties becoming an national important production component which is each of varieties have their own ecosystem. That's why the classification system is required. Classification engineered by adapting from data mining. The method that used is Modified K-Nearest Neighbor to predict a class from unclassified data. Based on the test that have been done the highest accuracy is 79,96% and the minimum accuracy is 51,2%.